PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI SMP MUHAMMADIYAH 50 MEDAN BESERTA SOLUSI NYA: - Syamil Al fatah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Abstract : Islamic Religious Education is a conscious and planned effort in preparing students to recognize, understand, appreciate, to believe, have devotion, and have noble character. The purpose of Islamic Religious Education is to foster religious humans, which means humans who are able to carry out the teachings of Islam properly and perfectly, so that it is reflected in the attitudes and actions in all their lives. The scope of Islamic Religious Education includes harmony, harmony, and balance between human relations with Allah SWT, human relations with fellow humans.In the implementation of Islamic Religious Education in schools, many problems arise. Various problems that arise, can be related to problems that are internal, or external. Among the solutions offered to overcome the problems of Islamic religious education in schools is through a partial approach, optimizing the role of the affective domain and creating a religious climate in the educational environment.